2019
DOI: 10.3329/imcjms.v12i2.39661
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and drug prescribing patterns at a rural primary health care center of Bangladesh

Abstract: Background and objectives: World Health Organization (WHO) and the National Health Policy of Bangladesh have repeatedly been emphasizing on the use of essential drugs prescribed by generic names. The prescription monitoring studies provide a bridge between areas like rational use of drugs and evidence based medicine. Knowledge on distribution and burden of diseases in a community is essential for planning rational use of drugs in a community. The present study tried to determine the morbidity profile and drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…4 The study revealed that the average number of drugs per encounter was 2.6, which was higher than the optimal value but lower than PHCs in Bangladesh (3.31), Pakistan (3.4), and Egypt (2.5). 3,11,16 The maximum prescription (43%) contained three drugs, which is similar to PHCs in Madhya Pradesh, India, where maximum patients (37.3%) had three drugs. 17 The study showed a maximum of six drugs per patient.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…4 The study revealed that the average number of drugs per encounter was 2.6, which was higher than the optimal value but lower than PHCs in Bangladesh (3.31), Pakistan (3.4), and Egypt (2.5). 3,11,16 The maximum prescription (43%) contained three drugs, which is similar to PHCs in Madhya Pradesh, India, where maximum patients (37.3%) had three drugs. 17 The study showed a maximum of six drugs per patient.…”
Section: Discussionmentioning
confidence: 58%
“…The WHO strongly recommends prescribing in generic names as a safety precaution for patients because it identifies the drug clearly, enables better information exchange, and allows better communication between healthcare providers. 16 However, generic prescribing was low (60%) compared to PHCs of Pakistan (71.6%), Egypt (95.4%), and Madhya Pradesh, India (60.9%) and higher compared to PHCs of Bangladesh (45.6%) and a recent study of Nepal (57.52%). 3,10,11,16,17 In PHCs, 58 drugs were available for free as per government provision; therefore, whatever the brand name prescriber used in prescription, the medicines available in PHCs, of whichever brand name, are dispensed to the patient.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…10 This is lower than reported by Dahal et al (59.02%), 19 Ferreira et al (86%), 20 Desalegn et al (98.7%) 21 and Momtaz et al (45.6%). 22 WHO always promotes the use of generic name of medicines as they are cheaper than branded substitutes and have equal efficacy and potency. The lower rate in Nepal may be due to the influence of local and international pharmaceutical companies on physicians' decisions.…”
Section: Discussionmentioning
confidence: 99%